Comparison of Prophylactic Norepinephrine and Phenylephrine Infusions During Spinal Anaesthesia for Primary Caesarean Delivery in Twin Pregnancies: A Randomized Double-Blinded Clinical Study - Du W; Song Y; Li J; Zhou X; Xu Z; Liu Z (Drug Design, Development and Therapy, 2022)
Weijia Du,* Yujie Song,* Jiang Li, Xianjin Zhou, Zhendong Xu, Zhiqiang Liu Department of Anesthesiology, Shanghai First Maternity and Infant Hospital, Tongji University School of Medicine, Shanghai, 200092, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiqiang Liu; Zhendong Xu, Department of Anesthesiology, Shanghai First Maternity and Infant Hospital School of Medicine, Tongji University, No. 2699, West Gaoke Road, Shanghai, People’s Republic of China, Email drliuzhiqiang@163.com; btxzd123@126.comBackground: Norepinephrine has been associated with improved heart rate (HR) and cardiac output (CO) compared to phenylephrine as a treatment for post-spinal hypotension during caesarean delivery (CD) in singleton pregnancies. Our current study compared the effects of norepinephrine and phenylephrine in maintaining maternal hemodynamics after spinal anaesthesia in twin pregnancies during elective CD.Methods: This was a double-blinded, randomized, controlled study. From December 2017 to December 2018, 62 women with healthy twin term pregnancies undergoing elective CD under spinal anaesthesia were studied. Following spinal induction, either norepinephrine (6 μg/mL) or phenylepinephrine (75 μg/mL) was infused at 60 mL/h to maintain systolic blood pressure (SBP) near baseline until delivery. HR, SBP, systemic vascular resistance (SVR), and CO were collected using anaesthesia monitors and continuous-pulse waveform analysis. The primary outcome was maternal CO. Other parameters of maternal hemodynamics, umbilical cord blood gases, and adverse events were also compared.Results: Hemodynamic variables (CO, SBP, HR, and SVR) between spinal anaesthesia induction to skin incision were similar between the two groups (P = 0.889, 0.057, 0.977, and 0.416, respectively). The incidence of bradycardia was significantly higher in the phenylephrine group (69%) than in the norepinephrine group (24.2%, P< 0.001). Maternal nausea and vomiting, hypotension, reactive hypertension, and neonatal outcomes did not differ between the groups.Conclusion: When administered as a prophylactic fixed-rate infusion, phenylephrine and norepinephrine are both capable of maintaining maternal blood pressure following spinal anaesthesia in twin pregnancies. There were no differences in the maternal hemodynamics or foetal outcomes between women receiving norepinephrine and phenylephrine.Previous Presentations: Presented at the 51st Society for Obstetric Anesthesia and Perinatology Annual Meeting, Phoenix, Arizona, May 1– 5, 2019.Clinical Trial Number and Registry: No. ChiCTR-IOR-17013358.Keywords: caesarean section, hypotension, norepinephrine, phenylephrine, spinal anaesthesia, twins